2017
DOI: 10.1016/j.jegh.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence rates of diabetes mellitus in Saudi Arabia: An overview

Abstract: Further development are required to assess the health intervention, polices, guidelines, self-management programs in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
239
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(250 citation statements)
references
References 32 publications
10
239
1
Order By: Relevance
“…The incidence of both type 1 diabetes (T1D) and type 2 diabetes (T2D) is increasing steadily, both in the United States and worldwide. [1][2][3][4][5][6][7] The National Diabetes Statistics report, 2017 (www.cdc.gov/diabetes/pdfs/ data/statistics/national-diabetes-statistics-report.pdf) 8 estimates that as of 2015, 30.3 million people in the US have diabetes (T1D or T2D), with 23.1 million being diagnosed and 7.2 million being undiagnosed; 90% to 95% of these have T2D. In China, where diabetes prevalence is the highest worldwide, an estimated 110 million adults have diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of both type 1 diabetes (T1D) and type 2 diabetes (T2D) is increasing steadily, both in the United States and worldwide. [1][2][3][4][5][6][7] The National Diabetes Statistics report, 2017 (www.cdc.gov/diabetes/pdfs/ data/statistics/national-diabetes-statistics-report.pdf) 8 estimates that as of 2015, 30.3 million people in the US have diabetes (T1D or T2D), with 23.1 million being diagnosed and 7.2 million being undiagnosed; 90% to 95% of these have T2D. In China, where diabetes prevalence is the highest worldwide, an estimated 110 million adults have diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study conducted in Saudi Arabia to explore the factors influencing nurses’ knowledge acquisition in diabetes care and its management, a topic that will only become more important in coming years, given the high and rising prevalence of diabetes in the country (Alotaibi, Perry et al., ). However, this study found a lack of clarity, caused by overlapping roles in diabetes care and education between nurses and other diabetes care providers, and conflicting attitudes among nurses that could lead to misinformation and misconceptions about diabetes care.…”
Section: Discussionmentioning
confidence: 99%
“…Some (but not all) nurses saw a need for, and believed that they should have, a wider role in patient education. Given the high and rising prevalence of diabetes in Saudi Arabia and worldwide (Alotaibi, Perry et al., ) and its strong links to behavioural risk factors, involving members of the multidisciplinary team is important for the effective management of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is a growing health problem in Saudi Arabia as high incidence rates of type 1 diabetes across the country, with rates rising particularly amongst children [10][11][12]. According to the International Diabetes Federation, there are 16,100 children with type 1 diabetes aged 0-14 years in Saudi Arabia, with an incidence rate of 31.4 new cases per 100,000 populations [6].…”
Section: Discussionmentioning
confidence: 99%